«Lavoro e conoscenza» dieci anni dopo Attualità della lectio doctoralis di Bruno Trentin a Ca' Foscari - Casellato, Alessandro (Carte, Studi e Opere - Centro Trentin di Venezia, 2014)
Bruno Trentin kept a tense and emotional lectio magistralis at the graduation ceremony for the honoris causa degree which he was awarded by the same university where his father had worked as a lecturer, before Fascism had forced him into exile, Ten years later, in the same place, scholars of different disciplines and generations read that text again, and relate it with their research. Lavoro e conoscenza functions as a prism, from which several different colours come out, and then end up revealing the complex stratification of that same lesson which condenses indeed the thoughts and hopes of one of the most fascinating Italian intellectuals and politicians of the second half of the 20th century. This book and the conference proceedings collect the texts of Trentin's lectio and of the laudatio the university gave him.